PEREMPUAN DALAM PERSEPEKTIF TEOLOGI HINDU - I Made Dirghayusa Mendala (Pangkaja: Jurnal Agama Hindu, 2022)
Women have the virtue of thinking so that they are able to face all kinds of problems in their lives. With the problems in their lives, women often experience discrimination that befalls them both in their families and in society. Women have special rights that deserve respect, protection and respect not to be insulted or harassed. Along with the times, there have been various forms of changes in globalization experienced especially by women since before this modern era. The development of the world of technology and information makes women still considered weak creatures, so that women's emancipation emerges to maintain their position in the household. If in the past women only had household tasks in the household, now women can think creatively for a career in the household without eliminating the household tasks they have. Due to the influence of globalization experienced by women, women become more motivated so as not to be out of date. In this modern era, women should want to be respected so that there is no oppression in the family or in society. And women are often considered weaker creatures than men. Women have a role as a wife as religious executor (yadnya) which includes the implementation of the Panca Yadnya consisting of Dewa Yadnya, Pitra Yadnya, Rsi Yadnya, Manusa Yadnya and Bhuta Yadnya. Balinese women play an active role in development that is equal to men. Therefore, balinese women must continue to follow and improve their abilities through formal or informal education. In this activity, Balinese women not only raise the welfare of their families.